IDENTIFICATION OF SOME CARCINOGENIC POLYCYCLIC AROMATIC HYDROCARBONS IN BANGLADESHI VEHICLES EXHAUST TAR BY GAS CHROMATOGRAPHY-MASS SPECTROPHOTOMETER - M. Amzad Hossain; S. M. Salehuddin (Universitas Gadjah Mada, 2008)
A more sensitive GC-MS method has been established for the determination of some carcinogenic polycyclic aromatic hydrocarbons (PAHs) in vehicles exhaust tar samples. The tar samples were extracted using dichloromethane (DMC): n-hexane solvent mixture. A multi-layer clean-up (silica gel/sodium sulphate) column was used, followed by glass fiber filter (GFF) paper. The method was successfully applied to determine a number of PAHs present in exhaust tar sample of different vehicles of the Atomic Energy Centre, Dhaka, Bangladesh.